Anencephaly. Experience in San Bartolomé (1988-1997) Hospital - Sanuvañez, Álvaro (2015)
OBJECTIVE To determine rate, epidemiology and obstetrical pathology associated to anenchepaly, cases attended between january 1988 and April 1997. DESIGN: Retrospective descriptive cross-sectional study. RESULTS: Anencepbaly rate was 11,2 per 1000 live newborns. The 48 cases had similar numbers of males and females. abortion had previously ocurred in 33,3%, previous cesarean section in 14,5% and 39,5% carried their first pregnancy. most frequent associated pathologies were hydramnios in 41,6%, urinary tract infection in 20,8% and PROM in 12,5%; 91,7% pregnancies ended before 35 weeks and 83,4% by vaginal delivery; presentation was breech in 10, 4% and 52% were born dead. Weights varied from 280 g to 360 g. CONCLUSIONS: We present one of the bigbest anencephaly rates in our region Previous history showed nullipary, previous abortion previous cesarean section. It is advisable to folic acid in the periconceptional period and request urine culture and study of vaginal secretion in a pregnant women carrying an anencephalic fetus.